Cervical Cancers: An Updated Review for Nursing Intervention Protocols - Yahya, Huda Mohammed; Alhindi , Thuraya Mahmoud; Yahya, Maha Mohammed; Asiri, Fatimah Abdulla; Jubarah , Alaa Ahmed; Abdullah , Tahani Mohammed; Alharthi, Wardh Aoun; Al-Qahtani, Abdullah Awad Shujaa; Shar, Ashwaq Mohammed Albar; Alsharari, Fahad Qasem Mutlaq; ALESSAIMI, SANA MOHAIMEED (Journal of Ecohumanism, 2024)
Background: Cervical cancer remains a significant global health concern, ranking as the fourth most common cancer among women worldwide. It is primarily caused by the human papillomavirus (HPV), a sexually transmitted infection prevalent among sexually active individuals. Despite advancements in prevention and treatment, disparities in screening, early detection, and access to care persist, particularly among vulnerable populations. Primary prevention through HPV vaccination and secondary prevention via regular screening are critical to reducing the burden of cervical cancer. Aim: This review aims to provide an updated overview of cervical cancer, focusing on etiology, risk factors, nursing interventions, and long-term care strategies to improve patient outcomes and reduce disparities. Methods: The review synthesizes current literature on cervical cancer, including epidemiological data, risk factors, diagnostic approaches, treatment modalities, and nursing management protocols. Emphasis is placed on evidence-based practices for prevention, screening, and patient-centered care. Results: Cervical cancer is largely preventable through HPV vaccination and regular screening. However, barriers such as lack of awareness, cultural stigma, and healthcare access disparities hinder prevention efforts. Nursing interventions, including patient education, symptom management, and care coordination, play a pivotal role in improving outcomes. Multidisciplinary collaboration and long-term care plans are essential for addressing physical, emotional, and psychosocial needs throughout the cancer journey. Conclusion: Effective management of cervical cancer requires a holistic approach that integrates prevention, early detection, and patient-centered care. Nurses are instrumental in providing education, support, and advocacy to reduce disparities and enhance quality of life for patients. Future efforts should focus on expanding access to vaccination, screening, and culturally sensitive care to reduce the global burden of cervical cancer.